A new method for studying platelets, based upon the low-angle light scattering technique. 3. Aggregation hypersensitivity of platelets (ADP agonist) and search for corrective agents. Issue 2 (2006) - Mindukshev Mindukshev, Igor V. Igor V.; Goncharov Goncharov, Nikolay V. Nikolay V.; Shabanova Shabanova, Elena Yu. Elena Yu.; Ermolaeva Ermolaeva, Elena E. Elena E.; Mironova Mironova, Maria O. Maria O.; Radilov Radilov, Andrey S. Andrey S.; Jenkins Jenkins, Richard O. Richard O.; Krivchenko Krivchenko, Alexander I. Alexander I.
Abstract : A new method for studying platelets based on low-angle light scattering has previously revealed that platelets taken from pregnant women with preeclampsia are hypersensitive to ADP, with aggregation developing at concentrations of 7–15 nmol l −1 . The method has been applied to further studies in experimental toxicology and clinical pathology. Toxicological experiments with fluoroacetate (FA), an inhibitor of TCA cycle, showed that the platelet hypersensitivity could also be caused by energy depletion. In modeling experiments, the low-angle light scattering method was applied to assessment of potential corrective agents of the pathological states related to hypersensitivity of platelets. Sodium glutamate (SG) was shown to be a potent antiaggregant in vitro, and subsequent in vivo studies demonstrated that SG can apparently serve as anaplerotic agent and normalize the platelet status of rats intoxicated with FA. Donators of nitric oxide (NO), such as isosorbide-5′-dinitrate, can also normalize in vitro the hypersensitive status of platelets taken from the patients with preeclampsia.